Reduction in inappropriate MRI knee studies after implementation of an appropriateness checklist: Experience at a tertiary care centre. Issue 123 (February 2020) - Xu, S.S.; Berkovitz, N.; Li, O.; Garvin, G.
Highlights: Increasing volume of study requests in diagnostic radiology. Resource limitations, such as MRI, result in the need for appropriate triage of requests. Studies should offer clinicians additional information to change patient care. Appropriateness criteria checklists can help to significantly reduce inappropriate studies. Abstract: Purpose: To evaluate reduction in inappropriate knee MRI requests following implementation of a mandatory knee MRI appropriateness checklist. Methods: A retrospective review was performed at a single tertiary care centre. A knee MRI appropriateness checklist was developed based on the ACR Appropriateness Criteria and adherence from referring physicians was mandatory. Reports from 200 consecutive knee MRI studies one year prior to implementation were compared to 200 consecutive knee MRI studies following implementation. The presence of moderate or greater osteoarthritis on MRI reports was used as a marker for inappropriate knee MRIs. Patient demographics, wait times, number of knee MRIs, and number of all MRIs at our centre over a six month period post-intervention and pre-intervention were recorded. Differences between pre-intervention and post-intervention presence of moderate or greater osteoarthritis, patient demographics, wait times, and number of MRIs analyzed. Results: A significant decrease was found in moderate or greater grade osteoarthritis following intervention, decreasing from 36.5% to 20.5% (73 studies versus 41 studies, p = 0.023). Of these, the most profound decrease occurred in studies with severe osteoarthritis, with an 80 % decrease (35 studies versus 7 studies, p < 0.001). Post intervention, 48 % fewer knee MRIs were performed in the same time interval (652 studies pre-intervention versus 336 studies post intervention, p < 0.001). No significant differences were found in the patient demographics. Conclusion: Mandatory knee MRI appropriateness checklists are associated with a significant reduction in the number of inappropriate studies performed. Follow up studies will be required to assess long-term impact in a larger population.